Group psycho-education in patients with bipolar disorder associated with a dependency of toxic substances in patients who are in abstinence - Patricia González Alegre (Fundación para el Desarrollo de la Enfermería, 2009)
The high comorbility that exists among psychiatric disorders and addictive is important. In the latest years it is produced an increase of the sensibility related to this problem. A great deal it is due to the demand of Mental Health Services and also due to drug dependency, as a consequence of the lack of an integral approach. Because of this fact and because of the mentioned demand, we though it should be pertinent developing a research project in order to check if the carrying the psycho-educative preventive group project out in patients with a diagnose of bipolar disorder with an abuse of drugs history and/or dependency of toxic substance in abstinence at the moment influents in a positive way in the course of the number of relapses in the toxic consumption during at least six months subsequent to the intervention. And at this way, these patients will purchase a greater consciousness of the important of healthy habits in the bipolar disorder and the recovery in the toxic substance abuse. The program will be developed in an experimental research where the patients will be randomly assigned in group control/ experimentally, the intervention will last twenty sessions, each session will be an hour and a half long and will be held weekly. In these sessions we will deal with topics related to the psychiatric disorder and the toxic consume. At the same time we will bank on the development of practical relaxation workshops on in some of the sessions with the object of providing a resource in view of stress situations.